Clonally unrelated HL-type RS manifested as hemophagocytic syndrome: a case report and literature review - Xiaoman Zheng; Wenshuang Ding; Zhigang Zhu; Junping Li; Weijie Zhong (Frontiers in Oncology)
Hodgkin lymphoma variant of Richter syndrome (HL-type RS) is a very rare disease, in which chronic lymphocytic leukemia (CLL) or small lymphocytic lymphoma (SLL) is transformed into novel Hodgkin lymphoma. The most important prognostic factor of HL-type RS is the clonal relationship between HL-type RS and the preexisting CLL/SLL. Detailed confirmation of clonally unrelated HL-type RS cases have not been reported. To the best of our knowledge, this is the first case of HL-type RS confirmed as clone independent by a detailed comparison of immunoglobulin gene rearrangement clones and gene mutations. A 76-year-old man, diagnosed with SLL 1 year before transformation was treated with Zanubrutinib 3 months before transformation. When diagnosed with HL-type RS, he presented with symptoms of hemophagocytic syndrome. Positive therapeutic effects were achieved using a modified rituximab-doxorubicin, bleomycin, vinblastine, dacarbazine regimen in combination with Zanubrutinib. We also discuss a thorough review of the relevant literature we performed to help us better understand this rare disease.